ChemInform Abstract: First Single Crystal Growth and Structural Analysis of Superconducting Layered Bismuth Oxyselenide; La(O, F)BiSe2. Issue 45 (23rd October 2014) - Tanaka, Masashi; Nagao, Masanori; Matsushita, Yoshitaka; Fujioka, Masaya; Denholme, Saleem J.; Yamaguchi, Takahide; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract Single crystals of La(O, F)BiSe2 are grown by a CsCl flux method involving powders of La, Bi2O3, BiF3, Bi, Bi2Se3, and Se in the molar ratio of 6:1:1:1:1:9 corresponding to LaO0.5F0.5BiSe2 (evacuated quartz ampoule, 900 °C, 2 h; controlled cooling).